PERLINDUNGAN HUKUM BAGI NASABAH FINTECH STUDI DI DESA SIGERONGAN KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - ARI RAHMAD HAKIM BF; YUDHI SETIAWAN; DIMAN ADE MULADA (SOSIAL SAINS DAN TEKNOLOGI, 2022)
The development of fintech in Indonesia has made significant progress and is the most popular today. The presence of Fintech companies in Indonesia has a positive impact on the economic activities of the Indonesian people because the advantages of this business include the convenience and flexible payment methods so that they can be used not only for individual interests but also for micro, small and medium enterprises. This research aims to increase public awareness about legal protection for Fintech customers, especially in Sigerongan Village, Lingsar District, West Lombok Regency so that rural communities will avoid losses in this business. The result is that the people of Sigerongan Village feel very helped by the information and enlightenment about the importance of legal protection for Fintech customers, Fintech company legal responsibilities and dispute resolution efforts